Analisis Strategi Guru dalam Menggunakan Teknologi Berbasis Digital pada Pembelajaran PKN di SD Negeri 105322 - Aflah Husnaini Matondang; Nadia Syahfitri; Siti Fadilla; Tiara Ramadhani; Safran Hasibuan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Learning strategy refers to an educator planning a series of activities designed to achieve learning goals. It involves the use of various methods, techniques, and approaches to organize the learning process. The strategy must be in accordance with the needs and characteristics of students. In the educational context, learning strategies are the basis for teachers in designing effective and meaningful learning experiences for students. This includes selecting subject matter, determining appropriate strategies, and the required learning media. Digital-based technology in learning in elementary schools is a very useful advancement in the learning and teaching process where there are digital aspects of resource books, assignments, assessments and student attendance books that can be used in the school environment and become preschool infrastructure. And digital technology is a more effective communication tool when designing a more student-oriented environment where teachers can develop creative skills in digital science.